Bis[dichloro-?6-indaneruthenium(II)] chloroform solvate - Vieille-Petit, Ludovic; Therrien, Bruno; Süss-Fink, Georg (My University, 2002)
The title compd. was prepd. from RuCl3.3H2O and bicyclo[4.3.0]nona-3,6(1)-diene and its crystal structure detd. Crystals of the compd. are monoclinic, space group P21/c, with a 10.5187(10), b 11.6680(15), c 11.4020(10) Å, ? 99.793(11)°; Z = 4, dc = 1.972; R = 0.032, Rw(F2) = 0.089 for 2528 reflections. The indane ligands adopt an envelope conformation toward the Ru atoms. The dimeric chloro-bridged mol. has crystallog. inversion symmetry. [on SciFinder(R)]
Keywords: ruthenium chloro indane chloroform prepn crystal structure; mol structure ruthenium chloro indane chloroform